Low cardiac content of long-chain acylcarnitines in TMLHE knockout mice prevents ischaemia-reperfusion-induced mitochondrial and cardiac damage - Liepinsh, Edgars; Kuka, Janis; Vilks, Karlis; Svalbe, Baiba; Stelfa, Gundega; Vilskersts, Reinis; Sevostjanovs, Eduards; Goldins, Niks Ricards; Groma, Valerija; Grinberga, Solveiga; Plaas, Mario; Makrecka-Kuka, Marina; et al. (Free radical biology & medicine, 2021)
Increased tissue content of long-chain acylcarnitines may induce mitochondrial and cardiac damage by stimulating ROS production. N6-trimethyllysine dioxygenase (TMLD) is the first enzyme in the carnitine/acylcarnitine biosynthesis pathway. Inactivation of the TMLHE gene (TMLHE KO) in mice is expected to limit long-chain acylcarnitine synthesis and thus induce a cardio- and mitochondria-protective phenotype. TMLHE gene deletion in male mice lowered acylcarnitine concentrations in blood and cardiac tissues by up to 85% and decreased fatty acid oxidation by 30% but did not affect muscle and heart function in mice. Metabolome profile analysis revealed increased levels of polyunsaturated fatty acids (PUFAs) and a global shift in fatty acid content from saturated to unsaturated lipids. In the risk area of ischemic hearts in TMLHE KO mouse, the OXPHOS-dependent respiration rate and OXPHOS coupling efficiency were fully preserved. Additionally, the decreased long-chain acylcarnitine synthesis rate in TMLHE KO mice prevented ischaemia-reperfusion-induced ROS production in cardiac mitochondria. This was associated with a 39% smaller infarct size in the TMLHE KO mice. The arrest of the acylcarnitine biosynthesis pathway in TMLHE KO mice prevents ischaemia-reperfusion-induced damage in cardiac mitochondria and decreases infarct size. These results confirm that the decreased accumulation of ROS-increasing fatty acid metabolism intermediates prevents mitochondrial and cardiac damage during ischaemia-reperfusion. [Display omitted] •TMLHE gene deletion is associated with lower acylcarnitine concentrations in plasma and tissues.•Accumulated long-chain acylcarnitines induce ROS production during reperfusion.•I/R-induced mitochondrial ROS production was lower in TMLHE KO mouse hearts.•TMLD is a novel drug target for cardioprotection.